A preliminary study of cell-based bone tissue engineering into 3D-printed β-tricalcium phosphate scaffolds and polydioxanone membranes - L. Pitol-Palin; J. Moura; P. B. Frigério; F. R. de Souza Batista; S. Saska; L. J. M. Oliveira; E. Y. Matsubara; L. Pilatti; D. Câmara; N. Lizier; A. Blay; J. A. Shibli; et al. (Scientific Reports)
Abstract Treatment of complex craniofacial deformities is still a challenge for medicine and dentistry because few approach therapies are available on the market that allow rehabilitation using 3D-printed medical devices. Thus, this study aims to create a scaffold with a morphology that simulates bone tissue, able to create a favorable environment for the development and differentiation of osteogenic cells. Moreover, its association with Plenum Guide, through cell-based tissue engineering (ASCs) for guided bone regeneration in critical rat calvarial defects. The manufacturing and characterization of 3D-printed β-TCP scaffolds for experimental surgery was performed. Nine male rats were divided into three groups: β-TCP + PDO membrane (TCP/PG), β-TCP/ASCs + PDO membrane (TCPasc/PG), and β-TCP/ASCs + PDO membrane/ASCs (TCPasc/PGasc). A surgical defect with a 5-mm diameter was performed in the right parietal bone, and the defect was filled with the 3D-printed β-TCP scaffold and PDO membrane with or without ASCs. The animals were euthanized 7, 14, and 30 days after the surgical procedure for histomorphometric and immunolabeling analyses. 3D-printed β-TCP scaffolds were created with a 404 ± 0.0238 μm gyroid macro-pore and, the association to cell-based therapy promotes, especially in the TCPasc/PGasc group, a bone area formation at the defect border region and the center of the defect. The use of 3D-printed β-TCP scaffolds and PDO membranes associated with cell-based therapy could improve and accelerate guided bone regeneration, promoting an increase in osteogenic capacity and reducing the time involved in the bone formation process. Moreover, using ASCs optimized the bioceramics by increasing its osteoinductive and osteoprogenitor capacity and, even with the resorption of the printed scaffold, aided as a scaffold for mesenchymal cell differentiation, as well as in bone tissue formation.